The Roles of the Kisspeptin System in the Reproductive Physiology of the Lined Seahorse (Hippocampus erectus), an Ovoviviparous Fish With Male Pregnancy - Zhang, Huixian; Zhang, Bo; Qin, Geng; Li, Shuisheng; Lin, Qiang (Frontiers in Neuroscience, 2018)
The kisspeptin/GPR54 system plays a crucial role in the regulation of the reproductive axis in vertebrates. Male pregnancy and ovoviviparity are special reproductive phenomena among vertebrates. To better understand the neuroendocrine mechanisms of male pregnancy, cDNAs encoding kiss2 and GPR54 were cloned and functionally characterized from the lined seahorse, Hippocampus erectus, an ovoviviparous teleost with male pregnancy. The core mature peptide of seahorse Kiss2 is high conserved, but unique among vertebrate Kiss orthologs. In the phylogenic analysis, the seahorse Kiss clustered with the teleost Kiss2 clade. The kiss2 transcripts were shown to be widely expressed in various tissues, notably in the brain and gonad of the seahorse, while GPR54-2 mRNA was expressed exclusively in the brain. In addition, the brain kiss2 mRNA increased significantly at the early puberty stage of the male seahorse, and was reduced significantly at the pregnancy stage. Intraperitoneal administration of seahorse Kiss2-10 to sexual mature male seahorses could stimulate lutropin β (LHβ) and follitropin β (FSHβ) release and increase serum testosterone levels. In summary, we first identified the kisspeptin/GPR54 system in an ovoviviparous fish with male pregnancy, which might be involved in the regulation of the reproductive functions of pubertal onset, gonadal development, and male pregnancy via regulating the synthesis of both gonadotropic hormone (GtH) and testosterone.